Meningkatkan Aktivitas Dan Hasil Belajar Siswa Menggunakan Model PBL, TGT Dan Metode Eksperimen Siswa SD - Rahmi Wardianti; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2023)
A quality education should start at the basic level, one of which is the subject of IPA. IPA learning will have good learning outcomes when students are involved in the entire learning activity carried out. The realities that happen show different things because classroom learning is one-way, students lack the opportunity to develop knowledge and understanding of IPA concepts, student still low in curiosity, and learning is monotonous and boring because notvaried learning models. The objective of this study is to describe the activities of teachers and analyze student activity and student learning outcomes using the problem-based learning model, Team Games tournaments, and experimental methods. This study uses the type of class action research conducted four times in meetings with a total of 28 students in class V SDN Kelayan Dalam 7 Banjarmasin. The results of the study showed an improvement in each meeting, i.e., the teacher's activity achieved a score of 36 on the criterion of